MANAJEMEN PELAKSANAAN UPAH MINIMUM KOTA PEKANBARU TAHUN 2016 - Zulnoviana "; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Wages are one of the most sensitive aspects of employment. Different stakeholders see wages from different sides. Workers see wages as a source of income to meet the needs of the workers / laborers and their families. Psychologically wages can also create satisfaction for workers. On the other hand, employers see wages as one of production costs. The government sees wages, on the one hand, to ensure the fulfillment of a decent life for workers and their families, increases labor productivity, and increases people's purchasing power.The concept of theory used in this study is the management according to Prajudi Atmosudirjo which explains that in analyzing the implementation, we can see 4 (four) functions in the management of Planning, Organizing, Direction, Supervision. This study aims to find out about how the management of Minimum Wages Pekanbaru City Year 2016. This study uses qualitative research methods and data assessment descriptively. In this data collection using the technique Interview, Observation, and Documentation, using the informant as a source of information.The results showed that the management of Minimum Wages implementation Pekanbaru City in 2016 has not been able to run optimally and maximally. Planning undertaken by the Office of Manpower and Transmigration of Riau Province concerning Wages for Workers that employers should not pay wages under the Minimum Wage provisions of the City. But in the implementation of the plan itself is still a company in Pekanbaru City that does not pay the wage of workers / laborers in accordance with the City Minimum Wage has been set. This causes the non-fulfillment of decent living needs, should the workers' income be able to meet physical, non-physical and social needs, which include food, beverages, clothing, housing, education, health, old age pensions, and recreation. Companies in Pekanbaru City should pay wages in accordance with City Minimum Wages in order to meet the needs of workers / laborers in order to increase the Human Resources of workers / laborers. Factors that influence in the implementation of Minimum Wage Management Pekanbaru City Year 2016 namely: Competitiveness of companies, selling power, Inflansi.Keywords: Implementation, Designation and Controling